Fluoxetine treatment during the postpartal period may have short-term impacts on murine maternal skeletal physiology - Hannah P. Fricke; Hannah P. Fricke; Chandler J. Krajco; Molly J. Perry; Lauren J. Brettingen; Lella A. Wake; Julia F. Charles; Laura L. Hernandez; Laura L. Hernandez (Frontiers Media S.A., 2023)
Postpartum depression affects many individuals after parturition, and selective serotonin reuptake inhibitors (SSRIs) are often used as the first-line treatment; however, both SSRIs and lactation are independently associated with bone loss due to the role of serotonin in bone remodeling. Previously, we have established that administration of the SSRI fluoxetine during the peripartal period results in alterations in long-term skeletal characteristics. In the present study, we treated mice with either a low or high dose of fluoxetine during lactation to determine the consequences of the perturbation of serotonin signaling during this time period on the dam skeleton. We found that lactational fluoxetine exposure affected both cortical and trabecular parameters, altered gene expression and circulating markers of bone turnover, and affected mammary gland characteristics, and that these effects were more pronounced in the dams that were exposed to the low dose of fluoxetine in comparison to the high dose. Fluoxetine treatment during the postpartum period in rodents had short term effects on bone that were largely resolved 3 months post-weaning. Despite the overall lack of long-term insult to bone, the alterations in serotonin-driven lactational bone remodeling raises the question of whether fluoxetine is a safe option for the treatment of postpartum depression.